Bee Honey Modulates the Oxidant-Antioxidant Imbalance in Diethyl nitrosamine-Initiated Rat Hepatocellular Carcinoma - Naima Zayed Mohamed, Hanan Farouk Aly, Hatem Abdel moneim El-Mezayen, Hadeer E. El-Salamony (Journal of Applied Pharmaceutical Science, 2016)
Oxidative stress reflects the mechanism that contributes to initiation and progression of hepatic injury in a variety of liver disturbance. From here, there is a great demand for the expansion of agents with a potent antioxidant effect. The aim of this work is to approximate the efficiency of bee honey as a hepatoprotective and an antioxidant agent versus diethyl nitrosamine (DEN) motivate hepatocellular damage. The single intrapritoneal (IP) management of diethyl nitrosamine (50mg/kg followed by 2ml/kg CCl4) to rats, referred for the histopathological examination of liver sections of rats after induction and before treatment with honey showed that many well differentiated tumor cells were formed in the liver of rats also, the examined sections showed disorganization of hepatic lobular architecture and obvious cellular damage. A significant lift in the enzymatic activity of liver functions (AST, ALT, ALP), and gamma glutamyltransferase (GGT) which is a signal of hepatocellular damage. DEN stimulates oxidative stress, which was assured by increase lipid peroxidation level and hindrance in antioxidant enzymes (SOD, CAT, GPx, and GST) activities in the liver. The position of non-enzymatic antioxidants comparable reduced glutathione (GSH) was likewise set up to be slimmed down significantly in DEN inoculated rats. Also, we have studied the underlying mechanism and /or (s) of the therapeutic role of bee honey as hepatocarcinogenesis remediation through investigation the inflammatory biomarkers; α-fetoprotein (AFP) and α-fucosidase (AFU). The current results clearly showed that bee honey demonstrates good ameliorative and antioxidant capacity toward diethyl nitrosamine induced hepatocellular damage in rats.
Keywords: Hepatocarcinogenesis, Diethyl nitrosamine, Bee honey, Oxidative Stress.